Flame-retardant epoxy resin composite material with low candlewick effect and preparation method thereof
By aminating and flame retardant modification of glass fibers and combining appropriate resin components, the problem of difficult to balance the flame retardant properties and mechanical properties of epoxy resin composites is solved, and low wick effect and high production are achieved The effect of efficiency.
Patent Information
- Application Number
- CN202411372670.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-02-18
AI Technical Summary
It is difficult to take into account the flame retardancy and mechanical properties of existing epoxy resin composite materials. The increase in the amount of flame retardant will reduce the strength and toughness of the material.
By aminating and flame retardant modification of glass fibers, the flame retardant epoxy resin composite material with low wick effect was prepared using the flame retardant DOPO-PH, combined with the appropriate resin component ratio.
It effectively suppresses the "candle wick effect", reduces the amount of flame retardant, maintains the mechanical properties of the composite material, and improves production efficiency.
Smart Images

Figure CN119463415A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite material modification, and in particular to a flame-retardant epoxy resin composite material with low candle wick effect and a preparation method thereof. Background Art
[0002] Epoxy resin composite material is a new type of material with high strength, which makes it show excellent tensile and compressive resistance when subjected to external loads; compared with traditional metal materials, epoxy resin composite materials have lower density and lighter weight, which can greatly reduce the weight of the structure; in addition, epoxy resin composite materials have strong resistance to corrosive substances such as acids and alkalis, which enables composite materials to be used for a long time in harsh environments without damage. Not only that, epoxy resin composite materials also have good weather resistance and can maintain stable structural performance under various climatic conditions. Based on the above performance advantages, epoxy resin composite materials have been widely used in many fields such as energy, automobiles, ships, aerospace, construction, and chemicals. Especially in application scenarios where materials are required to have good flame retardant properties, epoxy resin composite materials are an indispensable part.
[0003] However, in composite materials, if the distribution of fibers or particles is uneven, or there are differences in the physical properties of the material such as the thermal expansion coefficient and thermal conductivity coefficient, the internal temperature field and heat flow field will show uneven distribution. This unevenness will cause a "wick"-like channel to be formed along the axis of the fibers or particles during the heat transfer from the high-temperature area to the low-temperature area, which is called the "wick effect". The "wick effect" refers to a phenomenon in which the heat transfer path inside the material is formed due to the uneven structure of the material under high temperature conditions. Specifically, heat is quickly transferred through the fibers or particles in the material, forming a heat transfer path similar to a wick, thereby accelerating the heat transfer speed, causing the local temperature of the material to rise, and increasing the fire hazard of the material. In order to achieve the flame retardancy of epoxy resin composites, a common solution is to add flame retardants to the resin during molding. However, due to the existence of the "wick effect", in order to achieve the flame retardancy of the composite material, the amount of flame retardant added must be increased. The addition of a large amount of flame retardant often reduces the mechanical properties of the composite material, so that the strength and toughness of the epoxy resin composite material are inhibited. In addition, the addition of flame retardants will also affect the curing speed of the material, thereby affecting production efficiency. Summary of the invention
[0004] The present invention aims to provide a flame retardant epoxy resin composite material with low candle wick effect and a preparation method thereof, so as to solve the problem that the epoxy resin composite material in the prior art cannot take into account both flame retardancy and mechanical properties.
[0005] To achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a flame-retardant epoxy resin composite material with low wick effect, which is obtained by mixing flame-retardant modified glass fiber and resin component in a mass ratio of 7.5-8:2-2.5; the resin component includes the following raw materials in mass parts: 90.4-97.4 parts of epoxy resin, 0.6 parts of curing agent, 2 parts of release agent, and 0-7 parts of flame retardant; the flame-retardant modified glass fiber is obtained by sequentially subjecting glass fiber to amino modification and flame-retardant modification.
[0006] Preferably, as an improvement, the glass fiber is modified by amino coupling agent, and the amount of amino coupling agent added is 1 wt %.
[0007] Preferably, as an improvement, the amino coupling agent is at least one of 3-aminopropyltriethoxysilane (KH550), 3-aminopropyltrimethoxysilane (APS), N(2-aminoethyl)3-aminopropylmethoxysilane (AAPS), and N(2-aminoethyl)3-propylaminomethoxymethylsilane (AEAPS).
[0008] Preferably, as an improvement, the temperature for amination modification is 60-100° C., and the reaction time is 1-2 min.
[0009] Preferably, as an improvement, the flame retardant DOPO-PH is used to modify the glass fiber to be flame retardant.
[0010] Preferably, as an improvement, the preparation method of DOPO-PH comprises the following steps:
[0011] S1, mixing 4-aminophenol, 4-hydroxybenzaldehyde and methanol, and stirring to obtain system I;
[0012] S2, adding methanol to system I and cooling in an ice-water bath to precipitate the product 2-[(phenylimino)methyl]phenol, filtering and separating the solid and washing with cold methanol;
[0013] S3, dissolving 2-[(phenylimino)methyl]phenol and DOPO in THF, heating and stirring the mixture to obtain System II;
[0014] S4. The white precipitate in system II was filtered and washed with cold THF, and then dried under vacuum to obtain white powder DOPO-PH.
[0015] Preferably, as an improvement, in step S1, the molar ratio of 4-aminophenol to 4-hydroxybenzaldehyde is 1:1-3, the stirring temperature is 50° C., and the stirring time is 5 h.
[0016] Preferably, as an improvement, in step S3, the molar ratio of 2-[(phenylimino)methyl]phenol to DOPO is 0.1 to 1:1; the dissolution process is completed in a nitrogen atmosphere at room temperature; the mixture is heated to 60° C. and stirred for 12 h.
[0017] Preferably, as an improvement, a method for preparing a flame-retardant epoxy resin composite material with low wick effect comprises the following steps:
[0018] Step 1: treating the glass fiber: performing amino modification and flame retardant modification on the glass fiber to obtain flame retardant modified glass fiber;
[0019] Step 2: Dipping: Mix the flame retardant modified glass fiber and the resin component in a mass ratio of 7.5-8:2-2.5, so that the glass fiber is fully impregnated with the resin;
[0020] Step 3: Molding: Curing and molding using a molding mold to obtain a flame-retardant epoxy resin composite material with low "wick effect".
[0021] Preferably, as an improvement, in step three, the molding conditions are mold temperatures of 130±10°C, 140±10°C, 150±10°C, and pultrusion speed of 0.4-0.7 m / min.
[0022] The principle and advantage of this solution are: in actual application, in this technical solution, in view of the problem that the "wick effect" and mechanical properties of glass fibers cannot be taken into account when used in composite materials in the prior art, the present invention modifies the surface of the glass fibers, performs amino modification on the glass fibers, and then performs flame retardant modification. In the flame retardant modification stage of the glass fibers, this technical solution applies the flame retardant DOPO-PH to the modification of the glass fibers for the first time. DOPO-PH can self-crosslink into carbon at a relatively low temperature and pyrolyze small molecules of polymer materials at high temperatures to form a carbon layer with high thermal stability. This makes the glass fiber material modified by this technical solution have a good "wick effect" suppression effect, and can further reduce the amount of flame retardant used in the material and maintain the mechanical properties of the composite material, improve the production efficiency of the flame retardant composite material, and achieve a balance of the three, which has outstanding economic effects and important significance in the industry.
[0023] Moreover, when the flame-retardant modified glass fiber is applied to the preparation of epoxy resin composite materials, the technical scheme comprehensively and systematically optimizes the formula and preparation process of the flame-retardant modified epoxy resin composite materials. Firstly, the flame-retardant modified glass fiber is used in the composition of the raw materials, which can reduce the amount of flame retardant added to the resin and reduce the influence of the flame retardant on the resin reaction molding. Moreover, through the amino modification and flame-retardant modification of the glass fiber, its compatibility with the resin material in the subsequent compounding can be guaranteed. In the optimization of the preparation process, the pultrusion speed of the flame-retardant composite material is improved, and the production efficiency is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic structural diagram of a flame retardant epoxy resin composite material processing system in an embodiment of the present invention.
[0025] Figure 2 This is a physical picture of the composite material of Example 1 of the present invention. Figure 3 This is a physical picture of the composite material of Example 1 of the present invention. DETAILED DESCRIPTION
[0026] The following is further described in detail through specific implementations, but the implementation of the present invention is not limited thereto. Unless otherwise specified, the technical means used in the following implementations are conventional means well known to those skilled in the art; the experimental methods used are all conventional methods; the materials, reagents, etc. used can all be obtained from commercial channels.
[0027] The figure marks in the drawings of the specification include: yarn frame 1, yarn ball 2, first tensioning wheel 3, first yarn dividing plate 4, amino modification pool 5, second yarn dividing plate 6, first reflux tank 7, first oven 8, second tensioning wheel 9, third yarn dividing plate 10, DOPO-PH pool 11, fourth yarn dividing plate 12, second reflux tank 13, second oven 14, third tensioning wheel 15, epoxy resin pool 16, dipping rod 17, fifth yarn dividing plate 18, third reflux tank 19, molding mold 20, mold heating device 21, first traction device 22, second traction device 23, cutting machine 24.
[0028] Program Overview:
[0029] A flame-retardant epoxy resin composite material with low candle wick effect is prepared by mixing flame-retardant modified glass fiber and a resin component in a mass ratio of 7.5-8:2-2.5; the resin component comprises the following raw materials in mass parts: 90.4-97.4 parts of epoxy resin, 0.6 parts of curing agent, 2 parts of release agent and 0-7 parts of flame retardant.
[0030] The curing agent is at least one of an amine curing agent, an acid anhydride curing agent, an acid-base curing agent, and a phenolic acid curing agent.
[0031] The release agent is at least one of hydroxy acid-modified polysiloxane internal release agent, amine-modified polysiloxane internal release agent, polyether-modified polysiloxane internal release agent, silicone release agent, and emulsified oil.
[0032] The flame retardant is a phosphorus-based flame retardant, specifically at least one of dimethyl methylphosphonate, diethyl ethyl phosphate, trichloroethyl phosphate, tris(2-chloropropyl) phosphate), bromine-based flame retardants (hexabromocyclododecane, hexabromobiphenyl), nitrogen-based flame retardants (melamine, dicyandiamide, guanidine salts), and inorganic flame retardants (zinc borate, aluminum hydroxide hydrate, barium metaborate).
[0033] A method for preparing a flame-retardant epoxy resin composite material with low candle wick effect comprises the following steps:
[0034] Step 1: Processing of glass fiber:
[0035] S1. Amino modification of glass fiber: 100 g of GF (glass fiber) was dispersed in ethanol / water (500 ml, the mass ratio of ethanol to water was 450:50), and 1 wt% of an amino coupling agent (at least one of 3-aminopropyltriethoxysilane (KH550), 3-aminopropyltrimethoxysilane (APS), N(2-aminoethyl)3-aminopropylmethoxysilane (AAPS), and N(2-aminoethyl)3-propylaminomethoxymethylsilane (AEAPS)) was added under high-speed stirring, and the reaction was carried out from room temperature to 60-100° C. for 1-2 min. After the reaction was completed, the mixture was filtered, washed, and dried at 80° C. to obtain the amino glass fiber GF-NH 2, Its structural formula is as shown in formula (I).
[0036]
[0037] S2. Preparation of DOPO-PH: 4-aminophenol (10.9 g, 0.1 mole), 4-hydroxybenzaldehyde (12.2 g, 0.1 mole) and methanol were placed in a three-necked round-bottom flask equipped with a magnetic stirrer. The resulting mixture was stirred at 50°C for 5 h under a nitrogen atmosphere. The product 2-[(phenylimino)methyl]phenol was precipitated by adding methanol (200 ml) and cooling the resulting solution with an ice-water bath, and then the solid was separated by filtration and washed with cold methanol. Then, 2-[(phenylimino)methyl]phenol (10 g, 0.05 mole) and DOPO (21.6 g, 0.1 mole) were dissolved in THF (100 ml) at room temperature under a nitrogen atmosphere. The mixture was heated to 60°C and stirred for 12 h. The resulting white precipitate was filtered and washed several times with cold THF, and then dried under vacuum. The white powder was marked as DOPO-PH, and the structural formula of DOPO-PH is as shown in Formula (II).
[0038]
[0039] S3. Synthesis of GF@DOPO-PH: GF-NH2 (100 g) was evenly dispersed in ethanol (500 ml, the mass ratio of ethanol to water was 450:50), and the DOPO-PH prepared in step 2 was dissolved in 100 ml of ethanol and slowly dripped into the above solution, wherein the addition amount of DOPO-PH was DOPO-PH / GF-NH2 = 1%-10% (mass ratio). After the addition was completed, the reaction was continued for 1-10 minutes. After the reaction was completed, it was filtered, washed, and dried at 80°C to obtain the flame retardant modified glass fiber GF@DOPO-PH, with a structural formula as shown in formula (III).
[0040]
[0041] Step 2: Dipping the flame retardant modified glass fiber and the resin component in a mass ratio of 7.5-8:2-2.5;
[0042] The resin component includes the following raw materials in parts by mass: 90.4 to 97.4 parts of epoxy resin, 0.6 parts of curing agent, 2 parts of release agent, and 0 to 7 parts of flame retardant.
[0043] The curing agent is at least one of an amine curing agent, an acid anhydride curing agent, an acid-base curing agent, and a phenolic acid curing agent.
[0044] The release agent is at least one of hydroxy acid-modified polysiloxane internal release agent, amine-modified polysiloxane internal release agent, polyether-modified polysiloxane internal release agent, silicone release agent, and emulsified oil.
[0045] The flame retardant is a phosphorus-based flame retardant, specifically at least one of dimethyl methylphosphonate, diethyl ethyl phosphate, trichloroethyl phosphate, tris(2-chloropropyl) phosphate), bromine-based flame retardants (hexabromocyclododecane, hexabromobiphenyl), nitrogen-based flame retardants (melamine, dicyandiamide, guanidine salts), and inorganic flame retardants (zinc borate, aluminum hydroxide hydrate, barium metaborate).
[0046] Step 3: Forming: Curing the mixture of flame-retardant modified glass fiber and resin with a forming mold to obtain a flame-retardant epoxy resin composite material profile with low "wick effect". The forming conditions are mold temperature of 130±10℃, 140±10℃, 150±10℃, and pultrusion speed of 0.4-0.7m / min. After forming, it can be cut to a fixed length using a cutting machine.
[0047] In this embodiment, the flame retardant epoxy resin composite material with low wick effect is manufactured by using a flame retardant epoxy resin composite material processing system, which includes a glass fiber amino modification unit, a DOPO-PH processing unit, a pultrusion unit and a cutting unit.
[0048] The glass fiber amination modification unit is used for amination modification of glass fiber, and includes a first tension wheel 3, a first yarn separation plate 4, an amination modification pool 5, a second yarn separation plate 6, a first reflux tank 7 and a first oven 8 arranged in sequence, and an amination modification solution (amino coupling agent KH550) is contained in the amination modification pool 5. A yarn rack 1 is fixed to the feed end of the amination modification unit, and a plurality of yarn balls 2 are placed on the yarn rack 1, so that multiple yarn balls 2 can be processed simultaneously, and the system operation efficiency can be ensured.
[0049] The DOPO-PH treatment unit comprises a second tension wheel 9, a third yarn separation plate 10, a DOPO-PH tank 11, a fourth yarn separation plate 12, a second reflux tank 13 and a second oven 14 which are arranged in sequence. The DOPO-PH tank 11 contains a DOPO-PH mixed solution.
[0050] The pultrusion unit includes a third tension wheel 15, an epoxy resin pool 16, a dipping rod 17, a fifth yarn dividing plate 18, a third reflow groove 19 and a forming mold 20, which are arranged in sequence. A first traction device 22 is arranged at the discharge end of the forming mold 20, and a mold heating device 21 for heating the forming mold 20 is arranged between the first traction device 22 and the forming mold 20. A second traction device 23 is arranged on the right side of the first traction device 22, and a cutting unit is arranged on the right side of the second traction device 23. A plurality of dipping rods 17 are arranged, and the plurality of dipping rods 17 are arranged in the epoxy resin pool 16 for full contact between the glass fiber and the epoxy resin.
[0051] The cutting unit is a cutter 24 .
[0052] When the flame retardant epoxy resin composite material is processed by the above processing system, first, the amination modification solution and the DOPO-PH mixed solution are respectively fed into the amination modification pool 5 and the DOPO-PH pool 11. Then, the glass fibers fixed on the creel 1 pass through the first tensioning wheel 3 and the first yarn dividing plate 4 and are immersed in the amination modification solution for amination modification, and then dried in the first oven 8.
[0053] The dried glass fiber is further pulled, flame-retardant modified by the DOPO-PH mixed solution and further dried by the second oven 14. The flame-retardant modified glass fiber is mixed with the resin material in the epoxy resin pool 16 to form a mixed system, which enters the molding die 20 and is heated and cured by the die heating device 21 to obtain a low "wick effect" flame-retardant composite material profile. The low "wick effect" flame-retardant composite material profile enters the cutting unit under the traction of the first and second traction devices 23 and is cut to a fixed length by the cutting machine 24.
[0054] Example 1
[0055] A flame retardant epoxy resin composite material with low candle wick effect is prepared by mixing flame retardant modified glass fiber and resin component in a mass ratio of 8:2; the resin component includes the following raw materials by mass: 97.4 parts of epoxy resin, 0.6 parts of curing agent, 2 parts of release agent, and 0 parts of flame retardant. After testing, the flame retardant grade of the flame retardant epoxy resin composite material with low candle wick effect is V1.
[0056] A method for preparing a flame-retardant epoxy resin composite material with low candle wick effect comprises the following steps:
[0057] Step 1: Processing of glass fiber:
[0058] S1. Amination modification of glass fiber: Disperse 100 g of GF (glass fiber) in ethanol / water (500 ml, the mass ratio of ethanol to water is 450:50), add 1 wt% of amino coupling agent KH550 etc. under high-speed stirring, raise the temperature from room temperature to 80°C for 1 min, after the reaction is completed, filter, wash and dry at 80°C to obtain amino glass fiber GF-NH2.
[0059] S2. Preparation of DOPO-PH: 4-aminophenol (10.9 g, 0.1 mole), 4-hydroxybenzaldehyde (12.2 g, 0.1 mole) and methanol were placed in a three-necked round-bottom flask equipped with a magnetic stirrer. The resulting mixture was stirred at 50°C for 5 h under a nitrogen atmosphere. The product 2-[(phenylimino)methyl]phenol was precipitated by adding methanol (200 ml) and cooling the resulting solution with an ice-water bath, and then the solid was separated by filtration and washed with cold methanol. Then, 2-[(phenylimino)methyl]phenol (10 g, 0.05 mole) and DOPO (21.6 g, 0.1 mole) were dissolved in THF (100 ml) at room temperature under a nitrogen atmosphere. The mixture was heated to 60°C and stirred for 12 h. The resulting white precipitate was filtered and washed several times with cold THF, then dried under vacuum, and the white powder was labeled as DOPO-PH.
[0060] S3. Synthesis of GF@DOPO-PH: GF-NH2 (100 g) was evenly dispersed in ethanol (500 ml, the mass ratio of ethanol to water was 450:50), and salicylaldehyde or 2,4-dihydroxybenzaldehyde was added; then ethylenediamine with the same molar mass as salicylaldehyde or 2,4-dihydroxybenzaldehyde was dissolved in 100 ml of ethanol and slowly dripped into the above solution. After the dripping was completed, the reaction was continued for 1 min. After the reaction was completed, it was filtered, washed, and dried at 80°C to obtain flame-retardant modified glass fiber.
[0061] Step 2: Mixing: mixing the flame retardant modified glass fiber and the resin component in a mass ratio of 8:2;
[0062] The resin component includes the following raw materials in parts by mass: 97.4 parts of epoxy resin, 0.6 parts of curing agent, 2 parts of release agent, and 0 parts of flame retardant.
[0063] The curing agent is an acid anhydride curing agent; the releasing agent is a hydroxy acid modified polysiloxane internal releasing agent; and the flame retardant is a phosphorus flame retardant dimethyl methylphosphonate.
[0064] Step three, molding, curing the mixture of flame-retardant modified glass fiber and resin using a molding mold to obtain a flame-retardant epoxy resin composite material profile with low "wick effect". The molding conditions are mold temperatures of 130°C, 140°C, and 150°C, and a pultrusion speed of 0.5m / min. After molding, it can be cut to a fixed length using a cutting machine.
[0065] Example 2
[0066] The difference between this embodiment and embodiment 1 is that: in this embodiment, a flame-retardant epoxy resin composite material with low candle wick effect is mixed with flame-retardant modified glass fiber and resin component in a mass ratio of 8:2; the resin component includes the following raw materials by mass: 93.4 parts of epoxy resin, 0.6 parts of curing agent, 2 parts of release agent, and 4 parts of flame retardant. After testing, the flame retardant grade of the flame-retardant epoxy resin composite material with low candle wick effect is V0.
[0067] Example 3
[0068] The difference between this embodiment and embodiment 1 is that: in this embodiment, a flame-retardant epoxy resin composite material with low candle wick effect is mixed with flame-retardant modified glass fiber and resin component in a mass ratio of 8:2; the resin component includes the following raw materials by mass: 90.4 parts of epoxy resin, 0.6 parts of curing agent, 2 parts of release agent, and 7 parts of flame retardant. After testing, the flame-retardant epoxy resin composite material with low candle wick effect meets the MT113 standard.
[0069] Comparative Example 1
[0070] The difference between this comparative example and Example 1 is that in this comparative example, the amount of the flame retardant is 8%.
[0071] Comparative Example 2
[0072] The difference between this comparative example and Example 1 is that in this comparative example, the flame-retardant modified glass fiber is replaced by ordinary glass fiber that has not been modified.
[0073] Comparative Example 3
[0074] The difference between this comparative example and Example 1 is that in this comparative example, only the glass fiber is subjected to amino modification, and no flame retardant modification is performed.
[0075] Comparative Example 4
[0076] The difference between this comparative example and Example 1 is that in this comparative example, only the glass fiber is flame-retardantly modified, and no amino modification is performed.
[0077] Comparative Example 5
[0078] The difference between this comparative example and Example 1 is that in this comparative example, the glass fiber is treated with conventional flame retardant BDP when flame retardant modification is performed.
[0079] Comparative Example 6
[0080] The difference between this comparative example and Example 1 is that in this comparative example, when the glass fiber is subjected to amino modification, the coupling agent used is isopropyl tri(dioctyl pyrophosphate) titanate.
[0081] Comparative Example 7
[0082] The difference between this comparative example and Example 1 is that in this comparative example, the flame-retardant modified glass fiber is replaced by ordinary glass fiber that has not been modified, and the amount of the flame retardant is 35%.
[0083] Comparative Example 8
[0084] The difference between this comparative example and Example 1 is that in this comparative example, the flame-retardant modified glass fiber is replaced by ordinary glass fiber without modification, the amount of flame retardant is 35%, and the pultrusion speed is 0.1 m / min.
[0085] Experimental Example 1 Mechanical Properties Test
[0086] The flame retardant modified polyurethane composite materials prepared in the above embodiments and comparative examples were subjected to mechanical property tests, wherein the mechanical property test method was based on GB / T 3354. The results are shown in Table 1.
[0087] Experimental Example 2 Flame retardant performance test
[0088] The flame retardant modified polyurethane composite materials prepared in the above embodiments and comparative examples were tested for flame retardant properties, wherein: the flame retardant properties test method refers to GB / T 2408-2008, ASTM D2863 and MT113; each group was repeated three times, and the results are shown in Table 1: The results show that the use of modified glass fiber can effectively reduce the amount of composite flame retardant used, improve production efficiency, and can take into account both the mechanical properties and flame retardant properties of the composite material. In addition, Figure 2 Shown is a physical picture of the composite material prepared in Example 1 of the present invention.
[0089] Table 1
[0090]
[0091]
[0092] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A flame retardant epoxy resin composite material with low candle wick effect, characterized in that: The flame retardant modified glass fiber and the resin component are mixed in a mass ratio of 7.5-8:2-2.5; the resin component includes the following raw materials in mass parts: 90.4-97.4 parts of epoxy resin, 0.6 parts of curing agent, 2 parts of release agent, and 0-7 parts of flame retardant; the flame retardant modified glass fiber is obtained by sequentially subjecting the glass fiber to amino modification and flame retardant modification.
2. The flame-retardant epoxy resin composite material with low wick effect according to claim 1, characterized in that: The glass fiber is modified by amino coupling agent, and the addition amount of the amino coupling agent is 1wt%.
3. The flame-retardant epoxy resin composite material with low wick effect according to claim 2, characterized in that: The amino coupling agent is at least one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, N(2-aminoethyl)3-aminopropylmethoxysilane and N(2-aminoethyl)3-propylaminomethoxymethylsilane.
4. The flame-retardant epoxy resin composite material with low wick effect according to claim 3, characterized in that: The temperature of amination modification is 60-100°C, and the reaction time is 1-2 minutes.
5. The flame-retardant epoxy resin composite material with low wick effect according to claim 4, characterized in that: The flame retardant DOPO-PH was used to modify the amino-modified glass fiber to make it flame retardant.
6. The flame-retardant epoxy resin composite material with low wick effect according to claim 5 is characterized in that: The preparation method of DOPO-PH comprises the following steps: S1, mixing 4-aminophenol, 4-hydroxybenzaldehyde and methanol, and stirring to obtain system I; S2, adding methanol to system I and cooling in an ice-water bath to precipitate the product 2-[(phenylimino)methyl]phenol, filtering and separating the solid and washing with cold methanol; S3, dissolving 2-[(phenylimino)methyl]phenol and DOPO in THF, heating and stirring the mixture to obtain System II; S4. The white precipitate in system II was filtered and washed with cold THF, and then dried under vacuum to obtain white powder DOPO-PH.
7. The flame-retardant epoxy resin composite material with low wick effect according to claim 6, characterized in that: In step S1, the molar ratio of 4-aminophenol to 4-hydroxybenzaldehyde is 1:1-3, the stirring temperature is 50° C., and the stirring time is 5 h.
8. The flame-retardant epoxy resin composite material with low wick effect and the preparation method thereof according to claim 7, characterized in that: In step S3, the molar ratio of 2-[(phenylimino)methyl]phenol to DOPO is 0.1 to 1:
1. The dissolution process is completed under nitrogen atmosphere and room temperature. The mixture is heated at 60° C. and stirred for 12 h.
9. The method for preparing a flame-retardant epoxy resin composite material with low wick effect according to any one of claims 1 to 8, characterized in that: The steps include: Step 1: treating the glass fiber: performing amino modification and flame retardant modification on the glass fiber to obtain flame retardant modified glass fiber; Step 2: Dipping: Mix the flame retardant modified glass fiber and the resin component in a mass ratio of 7.5-8:2-2.5, so that the glass fiber is fully impregnated with the resin; Step 3: Molding: Use a molding mold to perform curing and molding to obtain a flame-retardant epoxy resin composite material with low "wick effect".
10. The method for preparing a flame-retardant epoxy resin composite material with low wick effect according to claim 9, characterized in that: In step three, the molding conditions are mold temperatures of 130±10°C, 140±10°C, 150±10°C, and pultrusion speed of 0.4-0.7 m / min.
Citation Information
Cited By
Explosion-proof resin composite material and preparation method thereof
CN120082170A